Meningkatkan Motivasi Belajar Siswa Melalui Integrasi Self-Efficacy Bandura dan Tawakal Ibnu Qayyim - Zamhariroh, Nazila Mumtaza; Muhid, Abdul (An-Nuha, 2025)
This study explores the integration of Albert Bandura’s concept of self-efficacy with the principle of tawakal as explained by Ibn Qayyim in enhancing students’ learning motivation. Self-efficacy emphasizes strengthening students’ belief in their ability to achieve academic goals, while tawakal offers a spiritual dimension by teaching the importance of fully entrusting outcomes to Allah after making the best possible effort. Using a qualitative approach based on literature review, this study analyzes relevant sources on both concepts and examines their relevance within the educational context. The findings reveal that the integration of self-efficacy and tawakal promotes a more holistic form of learning motivation that encompasses cognitive, emotional, and spiritual aspects. These two concepts complement each other self-efficacy fosters confidence and optimism in one’s abilities, whereas tawakal provides inner peace and acceptance of results. The study concludes that applying this integrated approach can significantly enhance students’ motivation and academic performance in modern education.